Chemometric Methods for Simultaneous Determination of Candesartan Cilexetil and Hydrochlorothiazide in Binary Combinations - Diyar Salahuddin Ali (Journal of Analytical Methods in Chemistry)
Simple, accurate, precise, and cost-effective chemometric techniques for the measurement of candesartan cilexetil and hydrochlorothiazide in synthetic mixtures were improved and validated. H-point standard addition, Q-absorption ratio, and correction absorbance spectrophotometric techniques were utilized for the simultaneous determination of both medicines in real pharmaceutical formulations. A new calibration approach was implemented based on chemical H-point standards. This approach was developed to resolve significantly overlapping spectra of two analytes and provide direct correction of both proportional and constant errors caused by the matrix of the sample. The first method of simultaneous determination of candesartan cilexetil and hydrochlorothiazide was carried out using the H-point standard addition method at wavelengths 239 and 283. For the ratio of the absorption at two selected wavelengths, one of which is the isoabsorptive point and the other being the maximum of one of the two components, the second method absorption ratio method was utilized. In distilled water, the isoabsorptive point of candesartan cilexetil and hydrochlorothiazide occurs at 258 nm. λmax of hydrochlorothiazide is 273 nm, which is the second wavelength used. Lastly, the absorbance correction method was implemented. This approach is based on absorbance correction equations and uses distilled water as the solvent for the examination of both medicines. In NaOH/EtOH solvent, the absorbance maxima of candesartan cilexetil and hydrochlorothiazide are 250 nm and 340 nm, respectively. For both wavelengths, candesartan cilexetil and hydrochlorothiazide exhibited linearity over a concentration range of 1–46 μg/ml and 1–44 μg/ml, respectively, for H-point standard addition. The Q-absorption ratio approach provides linearity over the concentration ranges of 1–46 μg/ml at 273 nm for candesartan cilexetil and 1–29 μg/ml for hydrochlorothiazide, 1–46 μg/ml at 258 nm for candesartan cilexetil, and 1–44 μg/ml for hydrochlorothiazide. For hydrochlorothiazide, the linearity for the correction absorbance method was obtained throughout a concentration range of 1–46 μg/ml at wavelengths 250 and 340 nm and 1–44 μg/ml at wavelength 250 nm. The results of the analysis have been statistically and empirically supported by recovery studies. All methods yielded recoveries in the range of 96 ̶102% for both medications. The LOD ranged from 0.46 ̶0.94 μg/mL for hydrochlorothiazide and from 1.26 ̶2.40 μg/mL for candesartan cilexetil. The approaches were then used to quantify candesartan cilexetil and hydrochlorothiazide in pharmaceutical tablets.